MODEL-MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM INTEGRATIF BERBASIS SAINS - Misbahudin (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2018)
Integral-based learning of Islamic-based Islamic Religion can be done with various models, ranging from Problem Based Learning, Project Based Learning, Inquiry, ICT-Based and Team Teaching. Each model has its own advantages and disadvantages. Islamic Education Teachers, especially at the Higher Education level are required to master science-based learning model, with the aim that learning goes more easily and fun, especially with integrative modelKey Words: learning, PAI, Integrative, Science